(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This article investigates how the culturally constrictive notions of disability produce a discourse that is particularly pervasive in the interpretation of abortion and adoption practices. In particular, this article addresses the African American response to the socially- maintained clinical construction of blackness as a unifying genealogical, genetic, and psychological impairment in the American culture. In this concern, the theatre of Kia Corthron, an African American playwright, investigates the physical and psychopathological implication of racial disability for black women. The identified research gaps are related to how Corthron expands African American playwrights’ critique of the alignment of blackness with disability to investigate other symptoms of racial disability. In particular, Corthron’s Cage Rhythm and Come Down Burning contest the presentation of abortion and adoption as consistent definers of the socially- constructed racial disability of female blackness that entails deprivation of viable options for Black motherhood. In this regard, Corthron’s plays envision how disabled black women could mobilize their own terms of abortion or child relinquishment and adoption to invert the racially-motivated gynecological grounds that predispose the oppressive correlation of disability, abortion, and adoption.